ISOLASI DAN UJI POTENSI BAKTERI TANAH PERTANIAN BERASTAGI SUMATERA UTARA DALAM MENDEGRADASI FUNGISIDA ANTRACOL BERBAHAN AKTIF PROPINEB - Diah Sri Utami; Nunuk Priyani; Erman Munir (Saintia Biologi, 2013)
Isolation and potential Berastagi agricultural soil bacteria, North Sumatra in degrading propineb-based antracol fungicide has been conducted. The isolated bacteria were grown on Bushnell Hass Broth (BHB) containing 2% of propineb-based antracol fungicide with propineb as the active compound. The cultures have been grown on shaking incubator at 150 rpm for 21 days. The media BHB containing 2% of propineb-based antracol fungicide without bacteria was used as a control. The parameters observed were the growth bacterial, biosurfactant activity, biosurfactant concentration and the residues of propineb which were observed on day 0th, 7th, 14th and 21th. A total of sixteen bacterial isolates were isolated using selective media Bushnel Hass Agar (BHA) containing 2% propineb-based antracol fungicide​​. Two bacterial isolates which were CBA 02 and JBA 04 were selected for further test to determine their ability to degrade propineb. JBA 04 showed much higher ability in reducing propineb concentration up to 60.86%, while CBA 02 was only 5.59% than that of control.   Keywords: biodegradation, bioremediation, biosurfactant, fungicides, propineb